Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan pada Pusdiklat Gulkarmat Jakarta Timur - Maria Levina Felicia (Global Leadership Organizational Research in Management, 2025)
This study aims to analyze the influence of work environment and motivation on employee performance at the Gulkarmat Training Center in East Jakarta. The research sample consisted of 40 respondents taken using census techniques. Data were collected through a questionnaire using a Likert scale and analyzed with SPSS 27 using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results of the study indicate that partially, the work environment has a positive and significant effect on employee performance with a value of t count = 4.839 > t table = 2.021 and a significance of 0.000 < 0.05. Motivation also has a positive and significant effect on employee performance with t count = 4.840 > t table = 2.026 and a significance of 0.000 < 0.05. Simultaneously, the work environment and motivation have a significant effect on employee performance with F count = 151.448 > F table = 3.25 and a significance of 0.000 < 0.05. The coefficient of determination (R²) of 0.891 shows that 89.1% of employee performance variation is influenced by the work environment and motivation, while the remaining 10.9% is influenced by other factors outside this research model.